Incomplete crime as an object of humanization of the Russian criminal legislation - V. F. Lapshin; R. V. Kilimbaev (Правоприменение, 2021)
The subject. The article is devoted to the problems of simultaneous harmonization between the policy of humanization of the Russian criminal law and the reduction of the crime rate in society. The institute of incomplete crime is proposed as one of the promising areas of humanization of criminal legislation. The authors analyze the norms of the Russian Criminal Code which determine the essence of an incomplete crime, as well as the specifics of imposing punishment for its commission. The subject of the research also includes the strategic provisions of the Russian legislation, which reflect the main directions of the implementation of contemporary criminal policy, its goal and objectives. The purpose of the article is to confirm or dispute hypothesis that it is inadmissible to criminalize the actions committed at the stage of preparation for the commission of an intentional crime, as well as it is admissible to mitigate the liability for attempted crime. Research methodology and techniques are represented by a number of general scientific and specific scientific methods of cognition, used primarily in humanitarian research. The establishment of regularities between the growth of crime rates and the degree of criminalization, determined in the current criminal legislation, is ensured by the use of the dialectical method of cognition. The methods of analysis and synthesis were used to compare statistical data on the state of crime in Russia and the dynamics of the number of convicts serving imprisonment. Various methods of formal logic were applied in the process of evaluating measures aimed at ensuring the humanization of modern Russian criminal legislation. The method of comparative legal research was used to study the content of the norms on responsibility for an incomplete crime. The result of the study is proof of the necessity to decriminalize actions that are currently defined as "preparation for the commission of a grave or especially grave crime." The necessity of a significant reduction in the degree of punitive criminal-legal impact on persons found guilty of an attempt to commit an intentional crime has been substantiated. Conclusions. It as expedient to partially decriminalize an incomplete crime and exclude this institution from the General Part of the Russian Criminal Code. This decision fully complies with the fundamental principles of criminal law: legality, guilt, justice, and will also ensure the effectiveness of the implementation of the modern policy of humanizing Russian criminal legislation.